2007
DOI: 10.1099/vir.0.82495-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of diverse rubella virus genotypes

Abstract: Based on the sequence of the E1 glycoprotein gene, two clades and ten genotypes of Rubella virus have been distinguished; however, genomic sequences have been determined for viruses in only two of these genotypes. In this report, genomic sequences for viruses in an additional six genotypes were determined. The genome was found to be well conserved. The viruses in all eight of these genotypes had the same number of nucleotides in each of the two open reading frames (ORFs) and the untranslated regions (UTRs) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
23
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 40 publications
8
23
1
1
Order By: Relevance
“…These values differ from those estimated for other species. The number of conserved sites in the human genome is ∼8% (48), and, in other viruses, the proportion is much higher, including 66% for HIV (49), 63% for influenza A virus (50), and 78% for rubella virus (51). These trends suggest that the number of invariant sites is inversely correlated with genome size.…”
Section: Discussionmentioning
confidence: 73%
“…These values differ from those estimated for other species. The number of conserved sites in the human genome is ∼8% (48), and, in other viruses, the proportion is much higher, including 66% for HIV (49), 63% for influenza A virus (50), and 78% for rubella virus (51). These trends suggest that the number of invariant sites is inversely correlated with genome size.…”
Section: Discussionmentioning
confidence: 73%
“…Prediction of the secondary structure elements revealed that the RUB NS protease Ca 2ϩ -binding loop was flanked by two helices, as observed in most EF-hand CaBPs (47). The predicted Ca 2ϩ -binding motif is highly conserved among the eight genotypes of RUB for which sequence of this region is available (72), including all of the Ca 2ϩ -binding coordination ligands (Fig. 1B).…”
Section: Vol 81 2007mentioning
confidence: 95%
“…Understanding of past transmission pathways may contribute to a better understanding of current risks of poliovirus spread from the remaining foci of endemicity. Similar analyses of other rapidly evolving RNA viruses, especially agents of vaccine-preventable diseases known to have significant transition biases (13,71,97), may aid in the development of improved strategies for their control.…”
Section: Discussionmentioning
confidence: 99%